2014
DOI: 10.1080/10962247.2014.955926
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity characteristics of dewatered sewage sludge by thermal hydrolysis reaction

Abstract: The purpose of this study is to quantify the thermal conductivity of sewage sludge related to reaction temperature for the optimal design of a thermal hydrolysis reactor. We continuously quantified the thermal conductivity of dewatered sludge related to the reaction temperature. As the reaction temperature increased, the dewatered sludge is thermally liquefied under high temperature and pressure by the thermal hydrolysis reaction. Therefore, the bound water in the sludge cells comes out as free water, which ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results are expressed in the final line of Table 2. Regarding thermal conductivity, the low value is also presented by [47,48]. The sewage sludge ashes' chemical characterization is presented in Table 3.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The results are expressed in the final line of Table 2. Regarding thermal conductivity, the low value is also presented by [47,48]. The sewage sludge ashes' chemical characterization is presented in Table 3.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The aim of this study is to assess the ability of quasi-active thermography to detect underside non-surface-penetrating defects lying over various substrates. In the present experimental work, garden soil was used to simulate scum because its relevant properties (i.e., density, thermal conductivity, and specific heat) are similar to those of solid scum, as summarised in Table 4 , where the thermal diffusivities of each material can be calculated through the given density, thermal conductivity, and specific heat [ 27 , 28 , 29 , 30 , 31 , 32 ]. Therefore, the membrane in this experiment was placed in contact with soil, water, and air to mimic, respectively, contact with scum, sewage, and biogas in the treatment plant.…”
Section: Ir Thermography Inspection Of Hdpe Geomembranesmentioning
confidence: 99%
“…The experiments described in Section 2.1 used clayey soil since it is reported that clayey soil has similar density [28,29], thermal conductivity [30,31] and specific heat [32,33] as scumbergs. The thermal properties of each material are summarised in Table 5.…”
Section: Finite Element Modelmentioning
confidence: 99%